2017
DOI: 10.21767/2472-5056.100031
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Xanthine Oxidoreductase and Xanthine Oxidase Activities in Plasma and Kidney Dysfunction

Abstract: Background: Oxidative stress (OS) is thought to play a role in detrimental events among patients with chronic kidney disease (CKD). Although the mechanism of OS increases in CKD patients is unclear, it has been suggested that increased activity of xanthine oxidase (XO), the superoxideproducing form of xanthine oxidoreductase (XOR), plays a large role in enhancing OS. Therefore, we measured the activities of plasma XOR and XO among CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
(32 reference statements)
1
14
1
Order By: Relevance
“…19,20 Xanthine oxidoreductase values reported in previous studies Even though plasma XOR activity is a new surrogate biomarker that reflects oxidative stress, some interesting articles on human plasma XOR activity have recently been published. [9][10][11]21,22 The first report on plasma XOR activity in humans by Otaki et al evaluated plasma XOR activity in 440 patients with chronic HF whose status was mainly NYHA class 10 In comparison with previous reports, the median value of XOR activity observed in the present study was extremely high at 104 pmol/h/mL. This suggests that patients with severely decompensated AHF suffered from excessive oxidative stress, which could have been caused by enhanced XOR activity during the acute phase.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…19,20 Xanthine oxidoreductase values reported in previous studies Even though plasma XOR activity is a new surrogate biomarker that reflects oxidative stress, some interesting articles on human plasma XOR activity have recently been published. [9][10][11]21,22 The first report on plasma XOR activity in humans by Otaki et al evaluated plasma XOR activity in 440 patients with chronic HF whose status was mainly NYHA class 10 In comparison with previous reports, the median value of XOR activity observed in the present study was extremely high at 104 pmol/h/mL. This suggests that patients with severely decompensated AHF suffered from excessive oxidative stress, which could have been caused by enhanced XOR activity during the acute phase.…”
Section: Discussioncontrasting
confidence: 49%
“…According to their analysis, XOR activity positively correlated with body mass index, serum UA levels, and high sensitive CRP, which is considered an important inflammatory biomarker. Terawaki et al reported that the mean XOR activity in 13 patients with CKD was 23.1 ± 15.9 pmol/h/mL 22. Furthermore, Nakatani et al reported that the mean XOR activity of 163 patients with end-stage renal disease on haemodialysis was 21.4 ± 13.5 pmol/h/mL and demonstrated that plasma XOR activity was associated with diabetes mellitus, leading to the conclusion that it may be necessary to reduce the ROS induced by enhanced XOR activity in patients with diabetes mellitus who required haemodialysis 21.…”
mentioning
confidence: 99%
“…Measurement of XOR and XO activities was performed by liquid chromatography combined with triple quadrupole mass spectrometry (LC-TQMS method). The detail of LC-TQMS method is described in a previous report [ 5 ]. Based on the XOR and XO activities obtained using the LC-TQMS method, the ratio of XO to XOR (XO/XOR) was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…XO is formed by reversible or irreversible oxidation of another isoform, xanthine dehydrogenase (XDH). Recently, we reported that XOR redox, which is defined as the ratio of XO to total XOR (XO and XDH), changes the oxidative condition in association with kidney dysfunction [ 5 ]. Because the XOR inhibitor (so-called “XO” inhibitor) allopurinol reduces CVD risk to approximately 30% among CKD patients [ 6 , 7 ], XOR redox and OS are thought to be closely related.…”
Section: Introductionmentioning
confidence: 99%
“…XO is the main enzyme involved in uric acid production, acting as the final metabolite of the adenine nucleotides. Simultaneously with the production of uric acid, XO activity liberates hydrogen peroxide and superoxide anion, well-established prooxidant molecules [34]. Increased plasma XO activity has been reported in several disease states, such as cholecystitis, shock, ischaemia-reperfusion injury, acute virus infection, adult respiratory distress syndrome, and carcinogenesis [28].…”
Section: Introductionmentioning
confidence: 99%